Cracking the Code: Shedding Light on Accounting Students' Career Intentions - An empirical study - Al Harsoosi, Eman Mubarak Sinan; Al Sulaimi, Mariya Khamis Marhoon; Thottoli, Mohammed Muneerali (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
The study aims to assess how a student's plan, perception, and family factors affect accounting students' career intentions. This research delves into the factors that influence accounting students' career intentions and investigates whether these factors evolve as they progress in their studies, ultimately shaping their workplace preferences. The study used a survey questionnaire asked on a 5-point Likert scale to gather primary data from 136 accounting university students studying in Oman. PLS-SEM has been employed in this study to conduct the analysis. The results showed that the determinants of accounting students' career intentions significantly affected students' plans. Likewise, students' perceptions are related considerably to accounting students' career intentions. Hence, the results showed that the p-values of the two independent variables, namely, students' plans and perceptions, significantly support the current study's hypotheses. However, the third variable, family factors, does not impact accounting students' career intentions